ANALISIS PENGARUH STRUKTUR KEPEMILIKAN MANAJERIAL, GROWTH OPPORTUNITY DAN CASH FLOW TERHADAP TIPE PEMBIAYAAN AKUISISI (Studi Empiris pada Perusahaan yang Terdaftar di BEI yang Melakukan Akuisisi Periode Tahun 2009-2014) - Afiffah, Dini Zahra; Arfianto, Erman Denny (Diponegoro Journal of Management, 2015)
This study aimed to examine the effect of managerial ownership structure, growth opportunity, and cash flow on method of payment in Acquisition by bidder.  Sample of this study used bidding companies listed on Indonesia Stock Exchange during 2009-2014. The sampling technique used in this research is purposive sampling method covering 44  companies as samples.        Hypothesis testing is using multinomial logistic regression models which the dependent variabel in categories. The category from method of payment consisted of cash financing, debt financing, and equity financing. The analysis method used in this study is Multicoloniarity Test, Overall Model Fit, Goodness of Fit Test, Coefficient of Determination Pseudo R-Square and multinomial logistic regression Analysis.Based on the results using multinomial logistic regression analysis, managerial ownership structure and cash flow has negative effect and no significant on equity financing. Growth opportunity that measured with Tobin’sQ has positif effect on equity financing.